2016
DOI: 10.9734/bjast/2016/23177
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Healthy and ex vivo Onychomycosis Nails and the Influence of a Porphyrin-propylene Glycol Antifungal Formulation

Abstract: Aims: To investigate nail penetration enhancing effectiveness of a novel drug formulation and ingredients, 40% propylene glycol (PG) and 40 µM multifunctional photosensitizer (MFPS). Proposed formulation was proven effective in photodynamic treatment (PDT) of ex vivo fungal infections of human nails (onychomycoses) and indirectly also to weaken nail's strength. Study Design: To directly proof the effect of the novel formulation on nail's hardness Atomic Force Microscopy (AFM) was employed to measure small-dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
(27 reference statements)
1
0
0
Order By: Relevance
“…Whilst these findings could appear in contradiction to ours the same authors reported that infected nails from patients (as those used in this work) presented a smoother topography than nails infected ex vivo, a difference apparently explained by the location where the infection originates. In ex vivo T. mentagrophytes-induced onychomycosis, the infection starts from the outer surface of the nail plate whereas in vivo, the infection infiltrates the internal side of the nail plate from the nail root and the eponychium [29,30]. This is consistent with our SEM microphotography of naturally infected specimens that showed hyphen in the ventral but not in de dorsal surface of the plate.…”
Section: Microstructure Of the Nail Surfacesupporting
confidence: 83%
“…Whilst these findings could appear in contradiction to ours the same authors reported that infected nails from patients (as those used in this work) presented a smoother topography than nails infected ex vivo, a difference apparently explained by the location where the infection originates. In ex vivo T. mentagrophytes-induced onychomycosis, the infection starts from the outer surface of the nail plate whereas in vivo, the infection infiltrates the internal side of the nail plate from the nail root and the eponychium [29,30]. This is consistent with our SEM microphotography of naturally infected specimens that showed hyphen in the ventral but not in de dorsal surface of the plate.…”
Section: Microstructure Of the Nail Surfacesupporting
confidence: 83%